Optimized Temperature Effect of Li‐Ion Diffusion with Layer Distance in Li(NixMnyCoz)O2 Cathode Materials for High Performance Li‐Ion Battery. Issue 4 (8th December 2015) - Cui, Suihan; Wei, Yi; Liu, Tongchao; Deng, Wenjun; Hu, Zongxiang; Su, Yantao; Li, Hao; Li, Maofan; Guo, Hua; Duan, Yandong; Wang, Weidong; Rao, Mumin; et al.
Abstract : Understanding and optimizing the temperature effects of Li‐ion diffusion by analyzing crystal structures of layered Li(Ni x Mn y Co z )O2 (NMC) ( x + y + z = 1) materials is important to develop advanced rechargeable Li‐ion batteries (LIBs) for multi‐temperature applications with high power density. Combined with experiments and ab initio calculations, the layer distances and kinetics of Li‐ion diffusion of LiNi x Mn y Co z O2 (NMC) materials in different states of Li‐ion de‐intercalation and temperatures are investigated systematically. An improved model is also developed to reduce the system error of the "Galvanostatic Intermittent Titration Technique" with a correction of NMC particle size distribution. The Li‐ion diffusion coefficients of all the NMC materials are measured from −25 to 50 °C. It is found that the Li‐ion diffusion coefficient of LiNi0.6 Mn0.2 Co0.2 O2 is the largest with the minimum temperature effect. Ab initio calculations and XRD measurements indicate that the larger Li slab space benefits to Li‐ion diffusion with minimum temperature effect in layered NMC materials. Abstract : The temperature effect for kinetics of Li‐ion diffusion in Li(Ni x Mn y Co z )O2 materials is investigated systematically. The Li‐ion diffusion coefficient of Li(Ni0.6 Mn0.2 Co0.2 )O2 is the largest with the minimum temperature effect. Ab initio calculations and experimental measurements indicate that the larger Li slab space benefits to Li‐ion diffusion with the minimum temperature effect in layered Li(Ni x Mn y Co z )O2 materials.